A multi-objective optimization model to the dynamic facility location in supply chain network design - Ali Abdi Seyedkolaei; Seyed Hadi Nasseri (تصمیم گیری و تحقیق در عملیات)
Purpose: One of the fundamental problems in the field of supply chain management is the problem of supply chain design. In this problem, the goal is to determine the location for establishing a number of facilities in different geographical areas to cover customers' demands.Methodology: The static and dynamic networks are considered to solve the problem. If the network is static, with the help of the iterated local search algorithm, the number and location of distribution centers are determined, and customers are assigned to each. If the network is dynamic, after determining the initial number and location of distribution centers and assigning customers to distribution centers, events related to network dynamics, such as customer decrease, customer increase, and variable size of demands, are investigated by customers. In addition, our proposed method considers the failure modes of network components. Also, the ability to survive the network can be seen in both network modes.Findings: The results obtained from the experiments were analyzed regarding evaluation criteria. The results of the experiments show the superiority of the proposed method compared to the CLSC and TSCFL methods.Originality/Value: The background investigation of the subject indicates that the design of multi-level supply chains and the issue of lesser-addressed facility locations have received less attention. In addition, facility dynamics and network survivability are not considered at the time of failure. Therefore, in this research, we have tried to reduce the cost by choosing the appropriate location of facilities and assigning customers to each of these facilities. Also, we will design the network so that it can be in a stable state and continue to operate when a network failure occurs.